STRATEGI PEMASARAN SWALAYAN PAMELLA DALAM PERSPEKTIF ISLAM (Studi Kasus Swalayan Pamella Yogyakarta Tahun 2010) - Arie Rachmat Sunjoto (JESI (Jurnal Ekonomi Syariah Indonesia), 2011)
This research is meant to scrutinize expansion strategy of Pamela Supermarket marketing at Yogyakarta Special Province, covering the marketing urgency for company demands and a marketing shift from conventional system to shari’ah-based one. In order to verify this work, the researcher utilizes surveys with purposive sampling method of 20 respondents who are knowledgeable and involved in expansion strategy of Pamela Supermarket marketing at Yogyakarta Special Province; and collects data through observation, questionnaires, interviews, and documentations which are analyzed by Internal-External Matrix and Analytical Hierarchy Process. JESIJURNAL EKONOMI SYARIAH  INDONESIAThe result of research shows that alternative strategic concept used to develop marketing strategy of Pamela Supermarket at Yogyakarta Special Province based on internal and external factors which are analyzed by Internal-External Matrix are: 1) development and improvement of cooperate networking intensity; 2) improvement of product distribution capacity; 3) improvement of product availability capacity; 4) people purchasing power; and 5) development of product diversification. Besides, according to further analyzed result by Analytical Hierarchy Process, priorities of expansion strategy of Pamela Supermarket marketing at Yogyakarta Special Province are: 1) to deal with government –industrial, trade and cooperative agency – to support business operations through workshops; 2) to create new concepts to attract consumers, add product variant, and promote products effectively; 3) to change merchandise position, add product variant, and give good service; 4) to develop product diversification, product distribution system, and work together with small and medium business in villages.To conduct alternative strategy of marketing requires coordination with government and private sectors of economic, social and political fields though the goal of Islamic economic is to pursue shari’ah values and build a blessed business.Keyword: Marketing Strategy, Distribution, Diversification